Air Quality and Its Effects on Acute Respiratory Infections Among Children Under Five in Jambi City: A Generalized Additive Model Approach - Sitanggang, Hendra Dhermawan; Kalsum, Ummi; Putra, Ashar Nuzulul (Media Publikasi Cendekia Indonesia, 2025)
Acute Respiratory Infections (ARI) are the leading cause of morbidity and mortality among children under five and a common reason for health service visits. The World Health Organization (WHO) recognizes air pollution as the greatest environmental threat to human health, including ARI risk. In Jambi City, the prevalence of ARI among children under five remains high, while air quality is of concern due to motor vehicle emissions, open waste burning, and forest fires. Air quality can have direct and indirect effects on ARI incidence. Previous studies in Jambi have analyzed ARI using individual-level data; research on broader patterns, trends, and air quality influence remains limited. This study aims to analyze the influence of air quality on ARI incidence in children under five in Jambi City. The study was a time series using monthly data on ARI prevalence, PM10, SO2, CO, O3, temperature, humidity, and rainfall. The results showed ARI cases were high at the beginning and end of each year, fluctuating from 2021 to 2023 with a marked increase in 2023. The final GAM model indicated a significant negative linear association for PM10 (p=0.04) and humidity (p=0.03). Carbon monoxide (CO) demonstrated a significant non-linear effect (edf=4.01, p=0.0005). Time (month), representing seasonal and long-term trends, showed the strongest non-linear association (edf=7.9, p=0.0001), reflecting seasonal variation in ARI incidence. Efforts are needed to raise awareness about ambient air quality, particularly PM10 and CO, so that parents remain vigilant outdoors with children. These findings highlight the importance of interventions, including emission control and education, to reduce ARI risk in under-five children.